Utilization of Ambulance Services and Associated Factors during Pregnancy and Labor Among Lactating Mothers in Buno Bedele Zone, Southwest Ethiopia - Rebuma Wirtu; Solomon Yeshanew; Abdi Geda (SAGE Publishing, 2023)
In Ethiopia, the use of ambulance services for urgent obstetric care improved institutional delivery and reduced maternal mortality. However, poor infrastructure, delayed response from dispatchers, and other socioeconomic factors influence service utilization. The present study assessed the utilization of ambulance services and associated factors during pregnancy and labor among lactating mothers in the Buno Bedele administrative zone of Southwest Ethiopia. Community-based cross-sectional study design with a sample of 792 lactating mothers was carried out. A multi-stage sampling technique was employed, and data were collected through structured questionnaire, and focus group discussions (FGD). Among the 792 study participants, 618 (78%) had antenatal care (ANC) follow up and 705 (89%) were aware of information on the availability of free ambulance services. Eighty one percent study participants requested for ambulance services, and 576 (79%) utilized during their pregnancy and delivery periods. Awareness of free ambulance service (AOR = 3, 95% CI [1.4, 7.1], P  = .006), maternal formal education (AOR = 3.9, 95% CI [1.46, 9.8], P  = .006) and ANC follow up (AOR = 4.5, 95% CI [8.9, 23.3], P  = .001) were identified factors responsible for enhanced ambulance services utilization in the study area. The finding of the present study revealed that pregnant women had a higher tendency to use ambulance services during their obstetric emergency. However, poor communication and road infrastructure, as well as delayed dispatcher response hampered better service utilization.